Oxidative Stress, Programmed Cell Death and Microcystin Release in Microcystis aeruginosa in Response to Daphnia Grazers - Rzymski, Piotr; Klimaszyk, Piotr; Jurczak, Tomasz; Poniedziałek, Barbara (Frontiers in Microbiology, 2020)
There is increasing evidence that programmed cell death (PCD) in cyanobacteria is triggered by oxidative stress and that it contributes to the survival of the cyanobacterial population such as Microcystis aeruginosa. At the same time, microcystins (MCs) released during cell lysis have been implicated in colony formation (enabled by the release of polysaccharides) in M. aeruginosa – a strategy that allows the effect of a stressor, including grazing to be avoided or decreased. This experimental research has explored whether extracts of Daphnia magna and D. cucullata (corresponding to 5, 25, 50 and 100 individuals per L) reveal the effect on the growth, intracellular reactive oxygen species (ROS) content, lipid peroxidation, PCD, MC-LR release and bound exopolysaccharide (EPS) level in M. aeruginosa during seven days of exposure. As demonstrated, extracts of both daphnids induced dose-dependent growth inhibition, increase in ROS levels, lipid peroxidation, and PCD. Moreover, the release of MC-LR and an increase in the bound EPS fraction were observed in treated cultures. Generally, the greatest effects were observed under the influence of D. magna extracts. The study indicates that grazer presence can potentially trigger a series of events in the Microcystis population; with cells undergoing oxidative stress-induced PCD associated with MC release which in turn increases EPS production by intact cells. As argued, this strategy is likely to have evolved in response to abiotic stressors, since both PCD and synthesis of MC in cyanobacteria predate the metazoan lineage. Nevertheless, it may still provide a benefit for the survival of the MC-producing M. aeruginosa population under grazer pressure.